Friend or Foe: the complexities of being an academic and a doctoral student in the same institution. Issue 9 (1st September 2020) - Clouder, Lynn; Billot, Jennie; King, Virginia; Smith, Jan
ABSTRACT: A growing expectation that academic staff in higher education institutions (HEIs) will be qualified to doctoral level can mean that doctoral study must be juggled alongside administration, teaching, and academic duties. Many academics study in their own institutions. We wished to explore their perspectives on (i) how the two roles, of being an academic as well as a doctoral candidate, interact or not and (ii) the influences and resources at play in navigating the processes. The qualitative study explored staff experiences in two HEIs in the United Kingdom and one in New Zealand. Using Cultural Historical Activity Theory (CHAT) as a theoretical framework, we identified the contradictions within and between academic life and doctoral candidature activity systems. However, we focus on the tools and rules that frame daily academic life and doctoral study, and suggest remodelling systems to be kinder to academic staff brave enough to engage in doctoral study.